Hydrogeology of the Table Mountain sandstone aquifer - Klein Karoo - Kotze, Johanita Christelle (University of the Free State, 2001)
Abstract not available
Thesis (Ph.D. (Geohydrology))--University of the Free State, 2001
Keywords: Groundwater -- South Africa -- Little Karoo; Hydrogeology -- South Africa -- Little Karoo